Maternal nutritional status modifies heat-associated growth restriction in women with chronic malnutrition. Issue 1 (27th January 2023) - Shankar, Kartik; Ali, Sumera A; Ruebel, Meghan L; Jessani, Saleem; Borengasser, Sarah J; Gilley, Stephanie P; Jambal, Puujee; Yazza, Deaunabah N; Weaver, Nicholas; Kemp, Jennifer F; Westcott, Jamie L; Hendricks, Audrey E; et al.
Abstract: Rapid changes in the global climate are deepening existing health disparities from resource scarcity and malnutrition. Rising ambient temperatures represent an imminent risk to pregnant women and infants. Both maternal malnutrition and heat stress during pregnancy contribute to poor fetal growth, the leading cause of diminished child development in low-resource settings. However, studies explicitly examining interactions between these two important environmental factors are lacking. We leveraged maternal and neonatal anthropometry data from a randomized controlled trial focused on improving preconception maternal nutrition (Women First Preconception Nutrition trial) conducted in Thatta, Pakistan, where both nutritional deficits and heat stress are prevalent. Multiple linear regression of ambient temperature and neonatal anthropometry at birth ( n  = 459) showed a negative association between daily maximal temperatures in the first trimester and Z -scores of birth length and head circumference. Placental mRNA-sequencing and protein analysis showed transcriptomic changes in protein translation, ribosomal proteins, and mTORC1 signaling components in term placenta exposed to excessive heat in the first trimester. Targeted metabolomic analysis indicated ambient temperature associated alterations in maternal circulation with decreases in choline concentrations. Notably, negative impacts of heat on birth length were in part mitigated in women randomized to comprehensive maternal nutritional supplementation before pregnancy suggesting potential interactions between heat stress and nutritional status of the mother. Collectively, the findings bridge critical gaps in our current understanding of how maternal nutrition may provide resilience against adverse effects of heat stress in pregnancy.